Biological inputs and agricultural policies in South America: between disruptive innovation and continuity - Goulet, Frédéric (Perspective, 2021)
Version française de l'article In South America, public policies take a strong interest in alternative technologies to agricultural chemical inputs (pesticides and fertilisers). Some South American countries support biological inputs, also known as bioinputs, through national incentive programmes and regulatory changes. Argentina, Brazil and Colombia are playing a leading role. However, the intention behind this promotion of bioinputs is not to break with industrial agricultural production models, from which States derive a large part of their tax income through exports. Rather, the goal is to foster coexistence between chemical and biological inputs in the context of a transition towards the bioeconomy. In this sense, the promotion of bioinputs meets the expectations of many South American farmers, as well as those of the agricultural inputs industry, which over the last few decades has diversified into these technologies. But these industrial dynamics are counter to certain farmers’ movements that defend on-farm production of biological inputs.